IMPLEMENTASI PEMBELAJARAN BERBASIS KKNI DI ERA REVOLUSI INDUSTRI 4.0 PADA PROGRAM STUDI PENDIDIKAN MATEMATIKA UNIVERSITAS HKBP-NOMENSEN PEMATANGSIANTAR - Christa Voni Roulina Sinaga; Lois Oinike Tambunan; Canni Loren Sianturi (Universitas Islam Sumatera Utara, 2020)
Frequent complaints about the gap between the number, quality and ability of graduates with the criteria needed by the world of work appear in the field and the still low Index of Technology Development, Information and Communication in Indonesia are two national problems that must be addressed carefully. In this regard, the Indonesian National Qualifications Framework (KKNI) policy is a solution that has been established by the government to improve the quality of Indonesia's human resources. In order to support the efforts to manifest Indonesian people who are superior and have global competitiveness, the researchers want to analyze the implementation of KKNI-based learning in the Industrial Revolution Era 4.0 in the Mathematics Education Study Program of HKBP Nommensen Pematangsiantar University (UHKBP-NP). It is hoped that this research can become a reference material for the government in reviewing and evaluating the effectiveness of the KKNI program so that different policies can be formulated according to the reality on the ground. This research problem will be revealed with a qualitative method approach because the things to be revealed are phenomenological. To collect all the required research data and information, the researcher will use three techniques, namely interviews; observation; and documentation. The data that has been collected will then be analyzed using focused observation techniques and interactive analysis techniques.